Structure and diversity of arboreal vegetation in coffee agroforestry systems in Sierra de Atoyac, Veracruz - García Mayoral, Luis E.; Valdez Hernández, Juan I.; Luna Cavazos, Mario; López Morgado, Rosalío (Instituto de Ecología, A.C., 2016)
Structure and tree diversity was studied in coffee agroforestry systems (SAF-café): rustic (RU), polyculture complex (PC), simple polyculture (PS), and as semi-evergreen forest (SM) from the Sierra de Atoyac, Veracruz, establishing three sampling units (UM) per altitudinal band (600-900 and 900-1200) m on each system and forest above mentioned, for a total 24 UM of 600 m2 (20 m x 30 m) each one. Each system was characterized by the diameter and height distribution of individuals as well as the calculated importance value (IVI), forest value (IVF), diversity (Shannon H ‘, α Fisher) and floristic similarity (Sorensen: Si) indices. To analyze patterns of species distribution of vegetation classification (cluster analysis: β flex) and ordination (canonical correspondence analysis: CCA) techniques were applied. 79 tree species were determined, richness per system was: SM= 65; PC= 61; RU= 32; PS= 18. Cordia alliodora (Ruiz & Pav.) Cham. was the most important structurally species in the SAF-café coffee and Myriocarpa longipes Liebm., and Bursera simaruba (L.) Sarg. in the SM. The diversity was significantly higher in PC (H ‘= 3.56) and SM (H ‘= 3.58) without significant differences (p < 0.05) between them. The highest floristic similarity was between SM and PC (Si = 0.69). Also the altitude was the most influential environmental factor in the floristic composition of the systems.